OSCE for year 4 MBBS IIUM set 1 - Hassan, Radhiana; Abd. Aziz, Azian; Md Ralib @ Md Raghib, Ahmad Razali; Che Mohamed, Siti Kamariah; Abdul Rahim, Mohamad Shahrir; Abidin, Mohd Radhwan (2020)
The article is a past year OSCE questions for end of posting examination.